Microbial Culture Collections and Microbiological Biobanks in the Context of New ISO Standards - Jaroszewska Ewelina; Nasiłowska Justyna; Sokołowska Barbara (Postępy Mikrobiologii, 2023)
In order to meet the growing needs of the world economy for biotechnology, culture collections must transform the way they operate from passive storage of microbial resources to active microbial resource centers whose services should go beyond the provision of microbes. The protection and conscious use of microorganisms aims to co-create a strategy for responsible and sustainable development, based on expert knowledge. This article deals with the subject of the recently developed panel of biobank-specific standards and the requirements that must be met by culture collections to transform into modern microbial biobanks.